GAYA BAHASA PENGULANGAN KISAH NABI MUSA AS. DALAM AL-QUR’AN: SUATU KAJIAN STILISTIKA - Mursalim, Mursalim (IAIN Samarinda, 2017)
Stories related to Moses are among the most frequently cited stories found in the Qur’an. This is, in part, due to the similarity of social context of Da’wa between Muhammad and Moses. Thus, the aim of this research is to understand how the Qur’an repeat those stories by stylistically scrutinizing each verses in the Qur’an related to Moses. This paper applies a combination of library research method using descriptive-analytical technique and maudu’I technique of Qur’anic interpretation. Findings of this research show that there are, at least, three linguistics styles in which the Qur’an repeat verses related to Moses; one related to using different linguistic styles, one related to using different actors, and one related to using different theme and chronological order. However, all of them revolves around the topic of advices for Muhammad in particular and humankind in general, in dealing with his social reality of Da’wa context.